The dilemma of Pituri: a review and case report. (27th September 2022) - Wan, M; Quinn, C; Butson, C; Kingon, A
Abstract: Smokeless tobacco is the term used to describe a range of products found worldwide which individuals use to extract nicotine, but without smoking. Ways of achieving this include chewing, sniffing and placing in areas of the body where tissues are sufficiently thin for absorption to take place such as the oral mucosa or postauricular skin. In Central Australia, Aboriginal groups across a wide area have chewed wild tobacco plants, commonly known as Pituri, for countless generations. As well as inducing a sense of well‐being, the habit has strong cultural significance. While some smokeless tobacco products used outside Australia are known to have a detrimental effect on oral health, particularly malignant change, little is known about Pituri . To date, reports of adverse oral outcomes have been elusive. Most Pituri research seems to have focussed on obstetric issues, arguably unexpected as the tobacco seems to be in contact with the mouth for longer than any other body tissues. The following report describes a lesion on the anterior buccal mucosa resulting from prolonged Pituri use. The relevant literature is reviewed. A clinical and ethical management dilemma arises between respecting the associated cultural issues and ignoring an apparent pathological entity. © 2022 Australian Dental Association.